The Effect of Strength Training Targeting Medial Thigh Muscles on Neuromuscular and Biomechanical Risk Factors for Anterior Cruciate Ligament Injury: A Randomized Controlled Trial - Jiyoung Jeong; Dai-Hyuk Choi; Choongsoo S. Shin (Sports Medicine - Open)
Abstract Background Knee valgus loading is thought to be an important contributor to noncontact anterior cruciate ligament (ACL) injuries, but the effects of training programs focusing on decreasing knee valgus loading on lower extremity biomechanics with respect to ACL injury risk remain unclear. Thus, this study aimed to examine the effect of strength training designed to strengthen the medial thigh muscles on lower extremity joint kinematics, kinetics and muscle activity during single-leg landing. Methods A total of 35 healthy participants randomly conducted either exercises targeting medial thigh muscles (intervention group) or exercises that did not target specific lower extremity muscles (control group). Three-dimensional hip, knee, and ankle kinematic/kinetic data and muscle activity for lower extremity muscles were obtained during single-leg landing. Two-way analyses of variance were conducted for each dependent variable to determine the effect of 8-week of strength training targeting medial thigh muscles. Results The intervention group showed decreased knee varus-valgus excursion (P = 0.009), peak valgus moment (P = 0.032), and peak hip internal rotation moment (P = 0.009) but increased gluteus medius activity in the precontact phase (P = 0.012) and vastus medialis-to-vastus lateralis (VM: VL) coactivation ratio in the postcontact phase (P = 0.043). The change in coronal plane knee excursion was negatively correlated with both the change in gluteus medius activity (R2 = 0.321, P = 0.014) and the change in VM: VL coactivation ratio (R2 = 0.276, P = 0.025). Conclusions Strength training targeting medial thigh muscles can modify the biomechanics associated with ACL injuries; thus, this intervention might be considered when designing ACL injury prevention programs to reduce dynamic knee valgus during sports-related tasks.